Spip Peran Dalam Peningkatan E-Procurement Dan Komitmen Organisasi Untuk Kurangi Fraud Pengadaan (Banten) - Millatina, Firda (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to examine and analyze the role of the Government Internal Control System to improve the implementation of e-procurement and organizational commitment in reducing the occurrence of fraud in government procurement of goods and services and its implications for government performance accountability in district/city governments in Banten Province. This research uses primary data in the form of a questionnaire with the research sample being UKPBJ and LPSE office officials in districts/cities in Banten Province who are directly involved in the goods/services procurement process. The sampling technique in this research used the Purposive Sampling method. In this research, the analysis techniques used are validity testing, reliability testing and hypothesis testing with the help of a statistical application in the form of Smart PLS 4. The results of this research prove that the implementation of e-procurement has a positive effect on Fraud in Government Procurement of Goods/Services, Organizational Commitment has a negative effect on Fraud in Government Procurement of Goods/Services, the Government's Internal Control System weakens the relationship between the Implementation of e-procurement and Fraud in Government Procurement of Goods/Services, The Government's Internal Control System strengthens the relationship between Organizational Commitment to Fraud in Government Procurement of Goods/Services, and Fraud in Government Procurement of Goods/Services has a Negative Influence on Government Performance Accountability.